The Oxford knee. Survival analysis of joint replacement. - Carr, A (1993)
To evaluate the success of a knee prosthesis, long-term follow-up studies are needed. The best means for this is survival analysis. It would be desirable for a contribution towards the costs of these essential follow-up studies to be included in the sale price of the prosthesis.